Living Ubuntu: the struggles of Abahlali Base Mjondolo as an African philosophy in the making - Motlatsi Khosi (University of Johannesburg, 2020)
What does it mean to engage in a philosophy of struggle and emancipation in our South African context? As part of my MA research I took an internship with Abahlali BaseMjondolo, a shack dwellers' movement whose office is based in central Durban. Their members reside in various settlements within KwaZulu Natal and the Eastern Cape. Whilst interning at the movement I conducted interviews with some of their members, using this experience to gain insight into the movement's theory and philosophy. Here I was challenged by what it means to do research using narrative as the foundation of my work. It is through narrative that one can tackle the problematic representations of black people in academia and society. I argue that in this movement a philosophy is at work. Their philosophy is based on the lived experience of struggle. As producers of knowledge, I argue that they represent the workings of Ubuntu. Using Maboge B. Ramose's (2002) explanation of 'Ubuntu as philosophy' I show how it can help us understand what it means to be human and how this is being affirmed in spaces of struggle. As agents of struggle we (black people) must be recognised for how we create knowledge. Ubuntu becomes the means through which we can map out the ways in such recognition can be understood and which an African philosophy is being being practiced. It is this recognition that is at the heart of the movement's philosophy of 'Abahlalism' which demonstrates the complexity of black experience in the space of social movement struggles. Key words: SOTL, scholarship of teaching and learning, Ubuntu, African philosophy, decolonial theory How to cite this article: Khosi, M. 2020. Living Ubuntu: The struggles of Abahlali Base Mjondolo as an African philosophy in the making. Scholarship of Teaching and Learning in the South. v. 4, n. 1, p. 26-36. April 2020. Available at: https://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=128 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/